Plan de negocio para la creación de una empresa comercializadora de artículos para la construcción en el sector en el paraíso la 14, año 2015 - Gavilánez Uribe, Sofía Stefanie (2015)
This research study aims to determine the feasibility of creating a trading company of building materials in terms of good living in order to identify weaknesses and threats in the local competitive market, so that they can strengthen those timely deficiencies through the implementation of a business plan. Paradise's 14 is an enclosure that is continuously growing in your neighborhood. Longtime there are two places where items and other building materials are sold, but these do not meet the consumer demand because no diversification. The overall objective of the work done is develop a business plan for the creation of a trading company of concrete products in order to position it in the enclosure Paradise 14th 2015. The 89% of respondents buy items for construction. This result is favorable for research as there is market demand. According to the data on supply and demand, it was determined that this business plan is viable due to the existence of an offer that does not meet the needs of people. To finance the hardware "Builder" is intended to make a claim in the Pichincha bank of $ 25,000 with an interest rate of 15% three-year term, $ 4,305.54 remaining will be provided by him / investors plan business. The financial evaluation yielded information on the profitability of the business plan, then its components are shown: the breakeven point for the first year is $ 75,217.90, 42% IRR, NPV and $ 32,469.68 B / C $ 1.30.